Pramūan phrarātchakaranīyakit Somdet Phranāng Čhao Siriki Phrab̨ōrommarāchinīnāt - Sirikit, Queen, consort of Bhumibol Adulyadej, King of Thailand, 1932- (Samnak Rātchalēkhāthikān, 1996)
Life and time of Sirikit, Queen, consort of Bhumibol Adulyadej, King of Thailand from 1950 to 1992; commemorative volume brought out at her 60th birth anniversary.